Activation of Sphingosine 1-Phosphate Receptor 1 Enhances Hippocampus Neurogenesis in a Rat Model of Traumatic Brain Injury: An Involvement of MEK/Erk Signaling Pathway. (29th November 2016) - Ye, Yuqin; Zhao, Zhenyu; Xu, Hongyu; Zhang, Xin; Su, Xinhong; Yang, Yongxiang; Yu, Xinguang; He, Xiaosheng
Abstract : Among sphingosine 1-phosphate receptors (S1PRs) family, S1PR1 has been shown to be the most highly expressed subtype in neural stem cells (NSCs) and plays a crucial role in the migratory property of NSCs. Recent studies suggested that S1PR1 was expressed abundantly in the hippocampus, a specific neurogenic region in rodent brain for endogenous neurogenesis throughout life. However, the potential association between S1PR1 and neurogenesis in hippocampus following traumatic brain injury (TBI) remains unknown. In this study, the changes of hippocampal S1PR1 expression after TBI and their effects on neurogenesis and neurocognitive function were investigated, focusing on particularly the extracellular signal-regulated kinase (Erk) signaling pathway which had been found to regulate multiple properties of NSCs. The results showed that a marked upregulation of S1PR1 occurred with a peak at 7 days after trauma, revealing an enhancement of proliferation and neuronal differentiation of NSCs in hippocampus due to S1PR1 activation. More importantly, it was suggested that mitogen-activated protein kinase-Erk kinase (MEK)/Erk cascade was required for S1PR1-meidated neurogenesis and neurocognitive recovery following TBI. This study lays a preliminary foundation for future research on promoting hippocampal neurogenesis and improving TBI outcome.